Comparison of 1-year clinical outcomes between prasugrel and ticagrelor versus clopidogrel in type 2 diabetes patients with acute myocardial infarction underwent successful percutaneous coronary intervention. Issue 11 (March 2019) - Ahn, Kye Taek; Seong, Seok-Woo; Choi, Ung Lim; Jin, Seon-Ah; Kim, Jun Hyung; Lee, Jae-Hwan; Choi, Si Wan; Jeong, Myung Ho; Chae, Shung Chull; Kim, Young Jo; Kim, Chong Jin; Kim, Hyo-Soo; et al.
Abstract : Abstract: Although the new oral P2Y12 inhibitors, prasugrel/ticagrelor have shown greater efficacy than clopidogrel in patients with the acute coronary syndrome, but they have not shown better efficacy in Korean patients. So we evaluated the efficacy of the prasugrel/ticagrelor in patients with myocardial infarction (MI) and diabetes, a more high-risk patients group. From the Korea Acute Myocardial Infarction Registry-National Institute of Health, 3985 patients with MI and diabetes who underwent PCI were enrolled between November 2011 and December 2015. The patients were divided into 2 groups: clopidogrel (n = 2985) and prasugrel/ticagrelor (n = 1000). After propensity score matching, prasugrel/ticagrelor group showed a no significant difference in risk of the composite of cardiac death (CD), recurrent MI or stroke (hazard ratio [HR], 0.705; 95% confidence interval [CI], 0.474–1.048; P = .084). However, the risk of major bleeding was significantly higher in the prasugrel/ticagrelor group. (HR; 2.114, 95% CI; [1.027–4.353], P = .042). In subgroup analysis, major bleeding was significantly increased in the subgroup of creatinine clearance <60 ml/min/1.73 m 2, hypertension, underwent a trans-femoral approach and diagnosed as NSTEMI among the prasugrel/ticagrelor group. The use of prasugrel/ticagrelor did not improve the composite of CD, recurrent MI or stroke, however, significantly increased major bleeding events in Korean patients with MI and diabetes undergoing PCI. Abstract : Supplemental Digital Content is available in the text